Incidental discovery of a copper-migrated intrauterine device in the rectum during abdominal hysterectomy - Diakhate, Abdoulaye; Wade, Mouhamadou; Niass, Ami; Ndiaye, Mame Diarra; Moreira, Philippe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The objective of the study is to report a case of IUDs migrating into the rectum that were accidentally discovered during an abdominal hysterectomy. This was a 47-year-old G9P8 patient with eight live vaginal births and one abortion dating back 7 years. As management, she would have received intrauterine suctioning followed by IUD insertion. The diagnosis of IUD migration was made during an abdominal hysterectomy for high grade cervical dysplasia CIN2. The migrating IUD perforated the right end of the posterior aspect of the uterine isthmus and the anterior aspect of the upper rectum. It was removed using forceps with its "T" that was lodged in the uterine wall and its body and thread in the rectum. The rectal breach was sutured with vicryl and total hysterectomy with bilateral adnexectomy could be performed without any other particularities. Migration of a copper IUD into the rectum is exceptional. However, it should be considered in a patient with digestive disorders in the days following the insertion of an IUD. The absence of the son should be a warning, and imaging and especially the digestive endoscopy allow the diagnosis to be made and at the same time its extraction to be carried out as soon as possible.